Prevalence of Hyperbilirubinemia in Preterm Neonates Admitted to the Nursery of Mufti Mehmood Hospital, Gomal Medical College, D.I. Khan - Khan, Sulaiman; Muhammad, Taj (Biological and Clinical Sciences Research Journal, 2025)
Pre-term neonates are known to be more susceptible to various forms of metabolic complications due to immature hepatic function. Hyperbilirubinemia is a common occurrence among pre-term infants and can lead to severe complications if not addressed. Objective: To determine the prevalence of hyperbilirubinemia in preterm neonates admitted to the nursery of Mufti Mehmood Hospital, Gomal Medical College, D.I Khan. Methods: This descriptive cross-sectional study was conducted from 10 October 2024 to 10 March 2025 in the Department of Pediatric Medicine, Mufti Mehmood Hospital, Gomal Medical College, D.I Khan. A total of 96 preterm neonates admitted within 7 days of birth were included. Serum bilirubin level more than 5 mg/dL with visible jaundice was taken as hyperbilirubinemia. Data were analysed using the Statistical Package for the Social Sciences version 26. Stratification was performed, and the chi-square test and Fisher’s exact test were applied. P-value ≤0.05 was considered significant. Results: Mean age was 4.14 ± 1.54 days, and mean gestational age was 32.17 ± 2.74 weeks. Hyperbilirubinemia was present in 48 (50%). Significant associations were found with age ≤4 days (69.6%, p<0.001), male gender (63.3%, p=0.008), gestational age ≤32 weeks (100%, p<0.001), and birth weight ≤2000 grams (100%, p<0.001). Conclusion: Hyperbilirubinemia is very common in preterm neonates. Lower gestational age and low birth weight are strongly related to this condition.